System of Development of Socio-Cultural and Educational Sphere in General Education Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Development and teaching technologies of sociocultural and educational spheres have been developed in comprehensive schools. The socio-cultural and educational sphere is a specially organized system of social-cultural and educational values and personal behavior aimed at solving various situations and problems in the process of education and the life of society in general.